Nikah Batin : Pandangan Ulama dan Stigma Bid’ah - Mutiara Dewi Lestari; Wahdinah; Shofia Ash Saudah; Nor Asifa (Indo Publishing, 2025)
The phenomenon ofspiritual marriage often sparks debate because it is considered valid spirituallybut does not comply with the pillars and requirements of marriage according to Islam.This study aims to examine the meaning of spiritual marriage, the traditional backgroundthat influences it, the views of scholars who consider it an innovation,and its social impact. The method used is aqualitative approach with a literature study through analysis of scholars' fatwas, scientific journals, and related Islamic legal literature. The results of the study indicate thatnikah batin without a valid contract has no basis in sharia law, has the potential tocause legal confusion, and is detrimental to the rights of women and children. This studysuggests the need for education on Islamic family law, the role of religious leaders, andimproved access to marriage registration to prevent the practice of nikah batin, whichcontradicts sharia law.